Study on rotation angle and three-zone deformation characterization of hinged structure of mining overburden rock based on OFDR - Qi LIU; Xianglin LIU; Guangyong CAO; Jinhai ZHAO; Changbao JIANG (Meitan kexue jishu, 2024)
In order to study the fiber optical strain characterization method of the overlying rock structure during mining in a certain mine in northern Shannxi, based on the engineering geological conditions of 12217 working face in Buertai Mine, the strain monitoring principle of OFDR ( Optical Frequency Domain Reflection Technology ) was analyzed. Based on the partition of mining-induced overburden movement state and the principle of distributed optical fiber strain monitoring, a mechanical analysis model of horizontal optical fiber strain to characterize the rotation angle of mining-induced overburden hinged structure was established. The functional relationship between the peak width of strain and the rotation angle of mining-induced overburden hinged structure formed after rock strata were broken was deduced, and the concept of critical rotation angle of hinged structure was defined. Based on the strain characteristics of optical fiber and the rotation angle of hinged structure of mining overburden rock, the criterion of three-zone division of overburden rock is proposed, and the strain characteristics of mining overburden rock are analyzed by means of optical fiber strain characterization method. The results show that the different deformation degree of the three zones of mining overburden is proportional to the rotation angle of the hinged structure, so it is feasible to divide the three zones by the rotation angle of the hinged structure. The rotation angle of the hinged structure is calculated by the peak strain characteristics of the horizontal optical fiber. Compared with the close-range photogrammetry angle of the two-dimensional physical similarity model test, the average error between the two is less than 1°, which verifies the effectiveness of the mechanical model of the proposed optical fiber strain to characterize the rotation angle of the hinged structure of the mining overburden. The height of the caving zone and the height of the fracture zone obtained by the two-dimensional physical similarity model are consistent with the field results of the working face and the theoretical calculation values, which are in line with the actual situation of the mine. The research results provide a new research idea for the application of distributed optical fiber monitoring technology to characterize the deformation characteristics of mining overburden.